Exploration of Obstacles and Key Roles in the Development of the Medical Tourism Industry - Roslina, Trias; Sulistiadi, Wachyu (Jurnal Multidisiplin Indonesia, 2025)
The medical tourism industry is currently experiencing rapid development in several countries. However, in some developing countries there are challenges to develop medical tourism. The author's goal is to critically assess the literature that examines the factors that are obstacles or challenges in the development of medical tourism as well as the potential strategies they present in their research. This study uses a systematic literature review taken from three databases; Pubmed, Scopus and Google Scholar. All studies taken from the results of the screening discussed the factors that are obstacles in developing medical tourism and presented potential strategies to overcome these obstacles. The results of the conclusion state that the role of the government is a key role in developing and promoting the medical tourism industry. The regulations that are built and the policies made by the government and stakeholders will be able to benefit the medical tourism industry which leads to an improvement in the economy and the welfare of its people. By properly managing and informing the policy-making and decision-making process, governments and industry stakeholders can drive the development and growth of these industries, resulting in the benefits of increasing the economy, including additional resources and revenues for healthcare investment in the country